DEVELOPMENT OF BASIC FINANCIAL ACCOUNTING E-BOOKLETS AS LEARNING MEDIA - Depi Pramika; Heri Pratikto; Madziatul Churiyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The utilization of e-booklets as learning media offers numerous advantages, serving as a digital resource to support the teaching and learning of fundamental concepts and principles in financial accounting. This research aims to develop an e-booklet on financial accounting fundamentals, intending to create a valid and practical learning medium. The method employed in this study is Research and Development (R&D) with the Rowntree development model, encompassing planning, development, and evaluation stages. The results demonstrate that the developed e-booklet on financial accounting basics has undergone rigorous validity testing and proves to be highly practical for educational purposes. This innovation presents an interactive learning medium that can be accessed conveniently online or offline through smartphones and other devices, paving the way for new opportunities in the field of education.